Study on Local Knowledge in Determining Site Suitability for Pepper Farm Establishment at Mongkos Area. - Azli Moni, Robbin (Universiti Malaysia Sarawak (UNIMAS), 2022)
Ethnopedology is a branch of indigenous knowledge that studies local people's knowledge in assessing soil fertility and suitability for agricultural uses, as well as rural people's soil and land use knowledge systems. Black pepper, (Piper nigrum L.) is from the family of Piperaceae also known as "the king of spices," is one of the world’s oldest and most extensively used spices. Sarawak Pepper has been chosen as the trade name and commercially used to promote Malaysian peppers globally. This study was carried out at Mongkos, Serian Sarawak. Most of the communities in this area are Bidayuh people and their main cultural activities are rice cultivation and cash crop farming (pepper, oil palm, rubber). There were two phase of data collection, phase 1 was interview with the farmers and phase 2 was soil sample collection. The interviews were conducted in the farm during farm visit before we collect the soil samples. Soil analysis consists of soil colour was determined by referred with Munsell Soil Colour Chart, soil texture by feel method, measurement of soil pH of H2O and Soil electric conductivity and determination of soil organic matter by the dry combustion method. In this study, 14 farmers that have been interviewed. Based on the interview and sampling that was conducted on the site, the farmers knowledge was divided into two category which is bad and good soil. The farmer assessment is based on soil colour, texture, rocks, moisture and moisture. Overall, soil physical properties analysis shows that there is no significance different between the good and bad soil. In conclusion, farmers classified soils based on their understandings and surroundings.